The impact of maternal supplementation during pregnancy and the first 6 months postpartum on the growth status of the next child born after the intervention period: Follow-up results from Bangladesh and Ghana - Adams, Katherine P.; Adu-Afarwuah, Seth; Mridha, Malay K.; Oaks, Brietta M.; Matias, Susana L.; Arnold, Charles D.; Kumordzie, Sika M.; Okronipa, Harriet; Ocansey, Maku E.; Dewey, Kathryn G. (Wiley, 2022)
This article was published in Maternal & Child Nutrition [ © 2020 The Authors. Maternal & Child Nutrition published by John Wiley & Sons, Ltd.] and the definite version is available at: https://doi.org/10.1111/mcn.12927 The Journal's website is at: https://onlinelibrary.wiley.com/doi/10.1111/mcn.12927